The Translation of Hebrew Flora and Fauna Terminology in North Sámi and West Greenlandic fin de siècle Bibles - Kahn, Lily (The Bible translator, 2019)
This study is a comparative analysis of the strategies employed in the translation of geographically specific flora and fauna terminology in the first complete Hebrew Bible translations into North Sámi (1895) and West Greenlandic (1900). These two contemporaneous translations lend themselves to fruitful comparison because both North Sámi and Greenlandic are spoken in the Arctic by indigenous communities that share a similar history of colonization by Lutheran Scandinavians. Despite this common background, our study reveals a striking difference in translation methods: the North Sámi translation exhibits a systematic foreignizing, formally equivalent approach using loan words from Scandinavian languages (e.g., šakkalak “jackals” from Norwegian sjakaler, granatæbel “pomegranate” from Norwegian granateple), whereas the Greenlandic translation typically creates descriptive neologisms (e.g., milakulâĸ “the spotted one” for “leopard”) or utilizes culturally specific domesticating, dynamically equivalent Arctic terms (e.g., kingmernarssuaĸ “big lingonberry” for “pomegranate”). The article assesses the reasons behind these different translation approaches.